(untitled) (Journal of Dhaka Medical College, 2021)
Approximately 80% ovarian tumorsare benign, and these arise mostly in young adult females. Malignant tumors are more prevalent in ageing women, between the ages of 45-65 years. Mucinous ovarian cancer represents about 5% of epithelial ovarian cancers (EOC).We have reported a case of mucinous cystadenocarcinoma in 35-year-old lady with metastasis to omentum.Imaging (radiograph & CT scan) studies showed a large right sided pelvic mass with probable origin in the right ovary. Cancer antigen-125 was elevated, while carcinoembrionic antigen and alphafetoprotein were normal. Mutational profiles shown distinct finding, as KRAS mutations positive nevertheless p53 and BRCA mutations are absent. She had undergone total abdominal hysterectomy with bilateral salphingo-oopherectomy along with pelvic dissection for removal of lymph nodes at the age of 35. She was given advice for radiotherapy with 3 cycles of chemotherapy with cisplatin and paclitaxel. To the best of our knowledge, this is the one of the littlecase of ovarian mucinous cystadenocarcinoma being reported at a relatively young age, and the first case being reported from Bangladesh. J Dhaka Medical College, Vol. 29, No.1, April, 2020, Page 83-88